Combining Fuzzy Dematel and Product Design Structure Matrix for Clustring Nozzle - Mahdi Karbasian; Mohamad Kazemi; Golara Iranpoor (مدیریت مهندسی و رایانش نرم)
This article presents an integrated approach for designing bullet fuzes. Using systems engineering in this approach, first of all the needs of the customer, Air Force, are considered and translated into functional requirements. Then, by applying the house of quality (HOQ) matrix, these functional requirements are transformed into component parts whose classification is finally carried out by the design structure matrix and through examining the presence or absence of relationship between various parts. On the other hand, regarding the different types of dependencies and relationships among these parts, the value and strength of relationships are expressed using fuzzy DEMATEL analysis that leads to the classification of components in each module. The integrated approach outlined in this article can serve as a basis for a fully localized process of designing and developing new products in design offices, resulting generally in reducing the design/redesign time and improving the quality. Furthermore, our novel approach is employed for the first time in single-function products causing changes in considering the types of relationships in the design structure matrix.